2000
DOI: 10.1037/0022-3514.79.3.385
|View full text |Cite
|
Sign up to set email alerts
|

From majority to minority and vice versa: The asymmetrical effects of losing and gaining majority position within a group.

Abstract: Two studies examined the effects of stable, partially changed, and completely changed majority and minority positions within a group on perception and evaluation of the group. It was hypothesized that loss of majority position (majority-to-minority change) would have stronger effects than gain of majority position (minority-to-majority change). The hypothesized asymmetrical effect was demonstrated in that loss of majority position decreased perception of group-self similarity, group attraction, and expectation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 45 publications
(61 reference statements)
5
49
0
Order By: Relevance
“…While most other studies of minority and majority influence used small groups mainly in laboratory settings (for example, Asch, 1955;Tanford and Penrod, 1984;Prislin et al, 2000), the present study was conducted within relatively large groups. When the group is large and individual group members cannot correctly estimate the numeric value of the majority and the minority subgroups, there is a perceived minimum group size that supports the individual's behavior rather than a numeric majority or minority.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…While most other studies of minority and majority influence used small groups mainly in laboratory settings (for example, Asch, 1955;Tanford and Penrod, 1984;Prislin et al, 2000), the present study was conducted within relatively large groups. When the group is large and individual group members cannot correctly estimate the numeric value of the majority and the minority subgroups, there is a perceived minimum group size that supports the individual's behavior rather than a numeric majority or minority.…”
Section: Discussionmentioning
confidence: 98%
“…Majority and minority subgroups constantly influence each other members' behaviors and attitudes (Smith, 1991;De Vries et al, 1996;Tan et al, 1998;Prislin et al, 2000), mainly through group norms and social pressure (e.g., Asch, 1955;Deutsch and Gerard, 1955;Kruglanski and Webster, 1991;Bond and Smith, 1996) and minority dissent (Moscovici, 1985(Moscovici, , 1976Nemeth, 1986). When exposed to majority influence, a minority is likely to experience substantial conformance pressure that causes it to focus on the majority position.…”
Section: The Influence Of Perceived Group Size On Adoption Behaviormentioning
confidence: 97%
See 1 more Smart Citation
“…For example, losing a majority position in a group (majority to minority) can have stronger effects than gaining a majority position (minority to majority) (Prislin, Limbert, & Bauer, 2000). Status is not a tangible possession; however status can be both a source of other resources (e.g., Lin, 1999;Thye, 2000) and a resource in and of itself (e.g., Barkow, 1989;Emerson, 1962).…”
Section: Status Gain and Lossmentioning
confidence: 98%
“…Studies on majority and minority (Prislin, Limbert & Bauer, 2000;Prislin & Christensen, 2005) clearly indicated that being part of the majority is attractive per se (Ellemers, Doosje, Van Knippenberg & Wilke, 1992;Simon & Hamilton, 1994), but also increases social status and positive social identity (Tajfel, 1981;Tajfel & Turner, 1986). In contrast, minority tends to be deprecated, stigmatized, and dismissed (Moscovici, 1994) thus the minority social identity is less attractive, unless active coping strategies are developed (De Dreu, Harinck & Van Vianen, 1999;Majory et al, 1998;Porter & Washington, 1993).…”
Section: Schism In Groups Characterized By a Majority And A Minoritymentioning
confidence: 99%